A Computational Comparison between Revetec Engine and Conventional Internal Combustion Engines on the Indicated Torque - Maisara Mohyeldin, Gasim Mohamed; Amirruddin, Abdul Kadir (WASET, 2011)

(untitled)
This paper investigates the effect of replacing crankshaft with cam on the indicated torque during compression and power strokes in internal combustion engines. A Cycloidal cam profile was used in Revetec engine to calculate and compare the torque to a conventional engine, using a computational method. Firstly, the cylinder pressure was calculated using Ferguson equation, and then the torque calculated depending on cylinder pressure values in every crank angle. the results showed that by using Cycloidal cam profile in Revetec engine the torque can increased by 14% compared with conventional engines, which means an increase in engine efficiency.